2014
DOI: 10.1080/0144929x.2014.945963
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levels of processing with navigation design types on recall and retention in e-learning environments

Abstract: The purpose of this study was to investigate the effects of levels of processing (LOP) and various navigation design types (NDTs) on high school students' recall and retention performances in e-learning environments. The participants' (N = 90) performances of free recall, title recognition, location memory and their retentions were measured in two different navigational layout design types by giving participants the instructional tasks which were designed in shallow, medium and deep LOP. Results are in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For example, panel position and menu structure were primarily studied in desktop context. As indicated by previous studies, a suitable menu position, such as left panel design (Torun and Altun 2014) and placement of well-designed intra-article navigation schemes (Cuddihy and Spyridakis 2012), could help in improving web navigation performance in terms of recall and retention. Besides, menu structure also matters.…”
Section: Menu-oriented Navigationmentioning
confidence: 93%
“…For example, panel position and menu structure were primarily studied in desktop context. As indicated by previous studies, a suitable menu position, such as left panel design (Torun and Altun 2014) and placement of well-designed intra-article navigation schemes (Cuddihy and Spyridakis 2012), could help in improving web navigation performance in terms of recall and retention. Besides, menu structure also matters.…”
Section: Menu-oriented Navigationmentioning
confidence: 93%
“…These challenges caused navigation problems but especially increased cognitive load for the human cognitive system (Altun, 2000). There is a significant effect of navigation design types on recall and retention in e-learning environments (Dikbas Torun & Altun, 2014). Therefore, this study indicated that it is important to fix these various navigation problems before implementation.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 86%